Holm Tetens on Panentheism: The Concept of Panentheism, Sin, and Special Divine Action - Göcke, Benedikt Paul (Neue Zeitschrift für systematische Theologie und Religionsphilosophie, 2017)
We briefly clarify Tetens’s concept of God and argue that there are some problems regarding both the precise formulation of his panentheism as well as its implications for sin and special divine action.